An Adaptive Logic Based on Jaśkowski's Approach to Paraconsistency - Meheus, Joke (Journal of Philosophical Logic, 2006)
In this paper, I present the modal adaptive logic AJ r (based on S5) as well as the discussive logic Dr2 that is defined from it. Dr2 is a (non-monotonic) alternative for Jaskowskis paraconsistent system D 2 . Like D 2 , Dr2 validates all single-premise rules of Classical Logic. However, for formulas that behave consistently, D2 moreover validates all multiple-premise rules of Classical Logic. Importantly, and unlike in the case of D2 , this does not require the introduction of discussive connectives. It is argued that this has clear advantages with respect to one of the main application contexts of discussive logics, namely the interpretation of discussions.